MUKIM CONCEPT ASGOVERNMENT ADMINISTRATORS IN ACEH - Mukhlis . (Faculty of Law, Universitas Jenderal Soedirman, 2015)
Abstract Mukim as administrators of Governance in Aceh was set by law and the qanun-qanun in Aceh, however be a resident of the organizing functions of governance have not been described in detail. This paper outlines the concept of Mukim as administrators in Aceh.The method used in this research is the study of normative law with specifications descriptive analytical study using normative juridical approach. Article114of LawNo. 11 of2006shall be clearly statedthat thegovernanceis composedofgovernmentmukimandtuha peutor another name. Related functions,completeness/device,the process of selecting/fillingpositionsand institutionsin mukimlevelset inqanundistrict/city and urban areas or district/city capital does not have to be formed mukim . Keywords: mukim, administrators, governance of AcehAbstrak Mukim sebagai penyelenggara pemerintahan di Aceh sudah diatur dalam undang-undang dan qanun-qanun di Aceh, namun fungsi mukim dalam menyelenggarakan pemerintahan belum dijelaskan secara terperinci. Tulisan ini menguraikan konsep mukim sebagai penyelenggara pemerintahan di Aceh. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normatif dengan spesifikasi penelitian deskriptif analitis yang menggunakan pendekatan yuridis normatif. Pasal 114 UU No. 11 Tahun 2006 perlu disebutkan dengan jelas bahwa Pemerintahan mukim terdiri dari pemerintah mukim dan tuha peut mukim atau nama lain. Lebih lanjut terkait dengan fungsi, kelengkapan/perangkat serta proses pemilihan/pengisian jabatan dan lembaga-lembaga di tingkat mukim diatur dalam qanun kabupaten/kota.Kata kunci:, mukim, penyelenggara, pemerintahan Aceh